REDUCING THE DATA TRANSMISSION TIME FROM GPU TO CPU BY GENERATING BIT MEMORY CARD - Vladimir Sergeevich Voronkin (Современная наука и инновации)
This article describes the research of algorithms of decreasing data transmission time from GPU to GPU by forming the bit memory card based on the results of calculations. Practical experiment showing the test results of the algorithm on different data quantities was performed.